Computer-Based Analysis of Visual Fields: Age-Related Norms for the Central Visual Field - Williams, T D (Canadian Journal of Optometry, 1983)
This paper will fulfill two purposes: A) To describe ways, means, and advantages of using computers to analyse two-dimensional clinical data (e.g. photographs, charts) so that the reader will have a clearer understanding of these methods and perhaps start considering applying them in practice. B) To present the results from a study of the central visual fields of 129 normal patients aged 10 to 70 years. These results are presented as average central fields for individual age groups ( 15, 25, 35, 45, 55, 65 years) so that the reader may compare a given patient's central field data to a norm for that patient's age group.